2017
DOI: 10.1093/arclin/acx003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sleep Loss on Subjective Complaints and Objective Neurocognitive Performance as Measured by the Immediate Post-Concussion Assessment and Cognitive Testing

Abstract: While self-report measures suggested marked impairments following sleep loss, deficits in neurocognitive performance were observed only on three domains measured with ImPACT. ImPACT may capture subtle changes in neurocognitive performance following sleep loss; however, independent and larger validation studies are needed to determine its sensitivity to acute sleep loss and recovery sleep. Neurocognitive screening batteries may be useful for detecting the effects of more severe or chronic sleep loss under high-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 68 publications
2
13
0
Order By: Relevance
“…Our results are in accordance with a relatively scarce literature showing an association between sleep problems and SCD (Kang et al., ; Stocker et al., ; Vaessen et al., ). Socioeconomic factors could play a significant role in the above association.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our results are in accordance with a relatively scarce literature showing an association between sleep problems and SCD (Kang et al., ; Stocker et al., ; Vaessen et al., ). Socioeconomic factors could play a significant role in the above association.…”
Section: Discussionsupporting
confidence: 94%
“…Of the studies that have examined sleep in relation to SCD, one study using both sleep questionnaire and polysomnography, as well as an extensive evaluation for SCD and the Immediate‐Post‐Concussion Assessment and Cognitive Testing battery showed that sleep loss was associated with increased severity of SCD (Stocker, Khan, Henry, & Germain, ). Poor sleep quality and daytime sleepiness were also linked to SCD in older adults, in two different studies: one using an objective neuropsychological battery (CERAD‐KN), a subjective memory complaints questionnaire, and a subjective sleep questionnaire (Pittsburg sleep index; Kang et al., ); and the other using both objective and subjective sleep measurement, a cognitive neuropsychological assessment and an SCD scale (Tardy, Gonthier, Barthelemy, Roche, & Crawford‐Achour, ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the King-Devick test, a measure of eye tracking, has been reported at ICC = 0.95 in a collegiate athlete sample [ 8 ]. Variable test performance can be associated with a number of factors including sleep [ 9 ], testing environment [ 10 ], and the test-retest interval [ 5 ]. While useful, each of the aforementioned studies has analyzed performance from relatively small cohorts and failed to include athletes from varying sexes, a wide breadth of sports, or skill levels.…”
Section: Introductionmentioning
confidence: 99%
“…Many medical conditions present with postconcussive-type complaints at levels that equal or even exceed the level observed in patients with concussion. Those conditions that have been directly evaluated for the presence of postconcussive complaints include: chronic pain ( Gasquoine, 2000 ; Smith-Seemiller et al, 2003 ) stress ( Machulda, Bergquist, Ito, & Chew, 1998 ) depression ( Donnell et al, 2012 ; Garden, Sullivan, & Lange, 2010 ; Trahan, Ross, & Trahan, 2001 ) anxiety ( Donnell et al, 2012 ; Garden et al, 2010 ; Lagarde et al, 2014 ) chronic fatigue syndrome ( Tiersky, Cicerone, Natelson, & DeLuca, 1998 ) orthopedic injuries ( Laborey et al, 2014 ; Landre et al, 2006 ; Losoi et al, 2016 ; Mickeviciene et al, 2004 ) sleep disruption ( Stocker, Khan, Henry, & Germain, 2017 ) …”
Section: Introductionmentioning
confidence: 99%